Design and Construction of a Pineapple Skin Cutting Machine with a Pneumatic Actuator Drive Powered by a Solar Module with a Capacity of 200 WP - Arizona, Rafil; Kurniadi, Shandy (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
The main objective of this research is to carried out the design of a pineapple cutting machine with a pneumatic actuator powered by a solar module with a capacity of 200 WP. The research methods used are literature study and experimental laboratory. The laboratory experimental method is very suitable to be applied to post-harvest agricultural machines with a small capacity where the research is only focused on the success of the actuator system in carrying out pineapple cutting movements automatically by utilizing pressurized air coming from the compressor. The variation in air pressure for the pneumatic actuator is set at the air pressure, namely 3, 4, and 5 Bar. The actual peeling capacity using air pressure of 3 Bar resulted in 160 pineapple cutting/per hour, 170 fruit/per hour for 4 Bar, 173 bar for 5 bar, and 173 fruit/per hour manually.